The Central Eastern European Countryside Transformation – Balance of Two Decades - Kwiecińska-Zdrenka, Monika (Eastern European Countryside, 2024)
Swain N. (2013), Green Barons, Force-of-Circumstance Entrepreneurs, Impotent Mayors. Rural Change in the Early Years of Post-Socialist Capitalist Democracy, CEU Press: Budapest–New York, pp. 398.